2007
DOI: 10.1111/j.1095-8649.2007.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by distance and selection effects on genetic structure of sardines Sardina pilchardus Walbaum

Abstract: Allozyme data were used to analyse the genetic structure of Sardina pilchardus populations. Fifty samples from 15 locations between the North Sea and Mauritania, including samples from the Azores, Madeira and the Mediterranean Sea, were surveyed. A weak but significant structure was found between all samples (F ST ¼ 0.057, P < 0Á001). This structure results from a change in the most common allele of SOD* between the North African and the Azores populations separated by the greatest distance. This locus seemed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 71 publications
(84 reference statements)
5
21
0
Order By: Relevance
“…The results of these studies, though not completely congruent, suggest a very weak genetic structure, with the exception of the allozymic locus SOD*, which could be subject to selection (Chlaida et al 2006;Laurent et al 2007).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results of these studies, though not completely congruent, suggest a very weak genetic structure, with the exception of the allozymic locus SOD*, which could be subject to selection (Chlaida et al 2006;Laurent et al 2007).…”
Section: Introductionmentioning
confidence: 91%
“…There have been a number of studies addressing the genetic structure of sardine in different parts of its global distribution, using different molecular markers such as allozymes (Spanakis et al 1989, Chlaida et al 2006, Laurent et al 2007, Chlaida et al 2009), mitochondrial DNA (Tinti et al 2002, Atarhouch et al 2006 and microsatellites (Gonzalez and Zardoya 2007a). The results of these studies, though not completely congruent, suggest a very weak genetic structure, with the exception of the allozymic locus SOD*, which could be subject to selection (Chlaida et al 2006;Laurent et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has commonly been reported for marine species of both invertebrates (Zouros and Foltz 1984) and fish (Waldman andMcKinnon 1993, Maggio et al 2009) and was often observed in pelagic fish (Laurent et al 2007, Gonzalez and Zardoya 2007a, Zarraonaindia et al 2009, André et al 2011. A homozygote excess may be explained as a consequence of evolutionary or technical processes, such as i) inbreeding; ii) selection; iii) the effect of mixing between different sub-populations (Wahlund effect); and iv) genotyping errors (i.e.…”
Section: Genetic Diversity and Deviation From Hardy-weinberg Equilibriummentioning
confidence: 97%
“…In addition, this fish species is one of the most abundant and one of the commercially most important in the Adriatic Sea (Santojanni et al 2005) and accounts annually for over US $32 million, with a peak of 90000 t landed in the early 1980s (Cingolani et al 2004). All the studies on sardine population genetics have shown low levels of genetic differentiation (Spanakis et al 1989, Laurent et al 2007, Gonzales and Zardoya 2007a, Kasapidis et al 2012, mainly suggesting the existence of differentiation between the Atlantic Ocean and the Mediterranean Sea (Atarhouch et al 2006). However, the Adriatic Sea seems to show differences in specific hydrological and oceanographic features (i.e.…”
Section: Introductionmentioning
confidence: 99%